Analisis Landasan Yuridis dalam Pendidikan Inklusi - Alhadi Alhadi; Priska Nuryani; Siti Rohimah; Opi Andriani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The purpose of preparing this article is to describe the juridical basis for inclusive education. This study uses a qualitative method. Data collection techniques include: observation using the Google Scholar search tool. The results of this research are that inclusive education is education that is friendly to all children, with an education service system that requires children with special needs to study in nearby schools in regular classes with friends their age. The juridical basis for inclusive education can be found in several laws and regulations and can be applied in schools with the principles of Law NO. 8 of 2016 Chapter III Part 6 Article 10 Concerning the Right to Education. States that, The right to education for Persons with Disabilities.